2013
DOI: 10.1080/13552600.2013.798689
|View full text |Cite
|
Sign up to set email alerts
|

An examination of implicit theories among francophone child molesters

Abstract: According to Ward (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 47 publications
(61 reference statements)
2
19
1
Order By: Relevance
“…The structure analysis indicates that the C-ISO scale represents a one-dimension model. This finding is contrary to previous research that conceptualized offense-supportive cognitions as a multidimensional construct (Gannon, Hoare, Rose, & Parrett, 2010; Marziano et al, 2006; Paquette & Cortoni, 2019; Paquette et al, 2014; Ward & Keenan, 1999). Very few studies have statistically tested these theoretical grouping of cognitions, and those who did failed to confirm their presence.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The structure analysis indicates that the C-ISO scale represents a one-dimension model. This finding is contrary to previous research that conceptualized offense-supportive cognitions as a multidimensional construct (Gannon, Hoare, Rose, & Parrett, 2010; Marziano et al, 2006; Paquette & Cortoni, 2019; Paquette et al, 2014; Ward & Keenan, 1999). Very few studies have statistically tested these theoretical grouping of cognitions, and those who did failed to confirm their presence.…”
Section: Discussioncontrasting
confidence: 99%
“…Although a number of independent studies have confirmed the presence of these cognitive themes, or variations thereof, in the statements made by men convicted of contact sexual offenses against children (e.g., Marziano, Ward, Beech, & Pattison, 2006; Paquette, Cortoni, Proulx, & Longpré, 2014), knowledge of the cognitions of men who committed online sexual offenses against children is much more limited. Although there are suggestions that these men share some of the general beliefs found among men who engage in contact sexual offending, such as the idea that sexual activities with children are harmless (Elliot, 2011), there are also findings that indicate the presence of cognitions specific to online offending, such as the use of child sexual exploitation material (CSEM) being driven by curiosity (Seto, Reeves, & Jung, 2010).…”
Section: Cognitions That Support Sexual Offendingmentioning
confidence: 99%
“…Although our i-version of the child as sexual being appears to be similar to the Bartels and Merdian’s child as sex objects implicit theory, results from our study suggest that children are rather seen as sexual human being than objects, as well as equal to them in their sexual interests and desires. Similar beliefs are also found among men with contact sexual offenses against children (Marziano et al, 2006; Milner & Webster, 2005; Paquette et al, 2014; Ward & Keenan, 1999), indicating that men with online offenses may be also quite similar to men with contact offenses in terms of their sexualisation of children.…”
Section: Discussionsupporting
confidence: 59%
“…These implicit theories would contain a number of distinct mental ideas and constructs, including assumptions about the desires, preferences, and beliefs of victims (Polaschek & Ward, 2002; Ward & Keenan, 1999). Although research on implicit theories did not permit to support the idea of existing underlying beliefs, results from thematic studies have however provided evidence for distinct mental ideas or cognitive constructs among various sexual offenders’ subsamples (e.g., contact child sexual offenders [Marziano et al, 2006; Paquette et al, 2014], rapists [Longpré & Cortoni, 2019; Polaschek & Ward, 2002], sexual murderers [Beech, Fisher, & Ward, 2005], female sex offenders [Beech, Parrett, Ward, & Fisher, 2009; Robitaille & Cortoni, 2014], and mentally ill offenders [Mannix, Dawson, & Beckley, 2013]). Some of these cognitions appear to be similar for different subgroups, including the idea that men who sexually offend are entitled to treat their victims as they please (e.g., see Entitlement in Polaschek & Ward, 2002; Ward & Keenan, 1999), whereas others appear to be unique to specific subgroups, such as the idea exhibited by men with contact offenses against children that sexual activities with children are harmless (e.g., see Nature of harm in Ward & Keenan, 1999).…”
Section: Defining Criminogenic Cognitionsmentioning
confidence: 99%
“…Men who sexually offend against children are presumed to hold a variety of beliefs about themselves, others, and the world which are hypothesized to facilitate their offending behaviors (Ward, 2000; Ward & Keenan, 1999). There is empirical evidence that these men express or endorse offense-supportive statements (e.g., Bumby, 1996; Marziano, Ward, Beech, & Pattison, 2006; Paquette, Cortoni, Proulx, & Longpré, 2014; Seto, Reeves, & Jung, 2010) and that endorsing an overall higher number of offense-supportive statements is associated with contact sexual offending (Helmus, Hanson, Babchishin, & Mann, 2013). Among men with online sexual offenses against children, initial studies provided knowledge on the content of cognitions they express (e.g., Bartels & Merdian, 2016; Howitt & Sheldon, 2007; Paquette, 2018), but none investigated whether specific types of cognitions are associated with their involvement in criminality.…”
mentioning
confidence: 99%